POSSIBILITIES OF APPLYING THE NETWORK TECHNOLOGY FOR MANAGEMENT OF EDUCATIONAL INSTITUTIONS - Сас, Наталья (SWorldJournal, 2021)
The author substantiates the possibility of using network technology to manage an educational institution. The author considers network interaction as a form of partnership - joint activities with a common goal and objectives with the pooling of resources